Model Regresi Spasial pada Proporsi Tenaga Kerja Perempuan di Provinsi Sulawesi Selatan - Mar'ah, Zakiyah; M, Mutiara; Pratiwi, Andi Citra (EKSPONENSIAL, 2025)
Female labor force participation in South Sulawesi, Indonesia, is an urgent issue in the context of economic development and gender equality. For this issue, spatial regression is performed to build the relationship between variables that influence female labor force participation in the region. This study performed the Spatial Autoregressive (SAR) model, which is a regression model where the response variable has spatial correlation. The value of Moran's I for the proportion of female labor force in South Sulawesi is 0.05125, meaning there is a positive spatial autocorrelation. The results obtained showed that the expected length of schooling and adjusted per capita expenditure have a positive effect and the average length of schooling has a negative effect on the proportion of female labor force in South Sulawesi.